Sexual dysfunction and its associated factors among patients with heart failure in public hospitals in Gondar town, North and West Gondar, 2024 - Mihret Melese; Mequanent Tiruneh Tassew; Gizachew Kassahun Bizuneh (BMC, 2024)
Abstract Introduction Sexual dysfunction is characterized by difficulties that interfere with achieving satisfying sexual activity, affecting desire, arousal, orgasm, and overall satisfaction. A recent study in Ethiopia identified heart failure as one of the most common cardiovascular diseases in the country. Sexual dysfunction significantly affects the quality of life in individuals with heart failure, yet it often goes underdiagnosed and underreported. Understanding the prevalence of sexual dysfunction and the factors influencing sexuality in these patients is essential. Therefore, the primary objective of this study was to determine the prevalence of sexual dysfunction among patients with heart failure in Gondar City and the northern and western zones of Gondar public hospitals. Method This study included 423 participants diagnosed with heart failure, selected through simple random sampling from January 3 to February 30, 2024. Data were collected using an interviewer-administered questionnaire covering socio-demographic, behavioral, and clinical information. Sexual dysfunction in males was assessed using the International Index of Erectile Function-5, while the Female Sexual Function Index-6 was used for females. Data were entered into Epidata version 3.6 and later exported to SPSS version 25 for analysis. Binary logistic regression was employed to identify factors associated with sexual dysfunction, with a significance level set at p ≤ 0.05. Result A total of 423 heart failure patients participated in the study, achieving a 100% response rate. The results indicated a significant prevalence of sexual dysfunction, affecting 57.92% of participants (95% CI 54.76%-63.76%). Female participants reported a higher prevalence of sexual dysfunction, with 63% of the 138 female heart failure patients affected. Among the 285 male participants, 55.4% (158 patients) were identified as having erectile dysfunction. Multivariable logistic regression analysis revealed that factors such as body mass index, age, insufficient physical activity, and smoking were significantly associated with sexual dysfunction in females. In males, erectile dysfunction was significantly linked to diabetes mellitus, heart failure classification, age, and insufficient physical activity. Conclusion and recommendation This study identified a high prevalence of sexual dysfunction, with females being more affected than males. Additionally, the research identified several factors influencing sexual dysfunction among patients with heart failure, including BMI, age, cigarette smoking, diabetes mellitus, and the classification of heart failure. The study recommends that healthcare providers and other stakeholders take proactive measures to alleviate the burden of sexual dysfunction in patients with heart failure. Strategies should focus on controlling the severity of heart failure symptoms, effectively managing comorbidities, and addressing factors such as body weight, psychological well-being, and behavioral patterns. By targeting these areas, healthcare providers can work toward minimizing the risk of sexual dysfunction and improving the overall quality of life for patients with heart failure.